Ethical Considerations of Influencing Behavior Using Computer Technology - Michael Bailey; Richard Hill; Albert Brown (International Journal of Ethics and Society)
Introduction: Computer technology and cyberspace have become an inseparable part of human life today and have affected all aspects of individual and social life. Today, the use of various psychological techniques in the design of products and services based on computer technology is being pursued seriously to gradually and unconsciously influence the behavior and mind of users, and frameworks have been developed in this direction to achieve this goal. This method of developing and designing technical artifacts based on computer technology will entail significant ethical considerations that require in-depth examination and analysis, which is addressed in the present article. Material and Methods: The method of this research is a philosophical analysis based on the use of common theories of moral philosophy and philosophy of technology. Conclusion: The unconscious influence on behavior using computer technology can be criticized from both the perspective of deontology and virtue-based moral perspectives. Even when the purpose of this influence is positive, the damage that is done to the user's autonomy makes these technologies morally reprehensible. In addition, the artifacts produced in this way are not value-neutral and are value-laden. Considering the inclusion of computer technology-based products and services in people's lives and the extent of the use of techniques for influencing behavior, it is necessary to take measures to combat the morally harmful effects of such artifacts. Improving the general literacy of users and also policy-making and regulation in the production of such products are suggested in this regard.